Point prevalence survey of antibiotic use in 26 Saudi hospitals in 2016 - Maher Al Matar; Mushira Enani; Ghada Binsaleh; Hala Roushdy; Deema Alokaili; Amira Al Bannai; Yasser Khidir; Hail Al-Abdely (Journal of Infection and Public Health, 2019)
Objective: To evaluate the antibiotic prescribing trends, qualitatively and quantitatively, among Saudi Ministry of Health (MOH) hospitals. Method and materials: In May 2016, information about the hospitals and patients was collected for all inpatients from 26 MOH hospitals in Saudi Arabia. Additional information about antibiotic treatment and infections was gathered. Data collection was done using Global Point Prevalence Survey (PPS) tool designed by University of Antwerp, Belgium. Results: A total of 3240 antibiotic doses were administrated to 2182 patients who represented 46.9% of the total eligible admitted patients. Of those patients on antibiotics, 510 (24%) patients were in the Intensive Care Unit (ICU), 646 (30.4%) patients were medically treated, and 972 (45.7%) patients were in surgical departments. The most commonly prescribed antibiotic group was third-generation cephalosporin (17.2%) and the most frequent indication was respiratory ract infectiont (n = 597; 18.2%). Antibiotics for surgical prophylaxis represented 23.4% of the total antibiotic doses. Of those, 78% were administrated for more than 24 hs. The rate of adherence to antibiotic guidelines was 48.1%. The indications for antibiotics were not documented in the patients’ notes for 51.1% of the prescriptions. Conclusion: This national PPS provided a useful tool to identify targets for quality improvement in order to enhance the prudent use of antibiotics in hospital settings. This survey can provide a background to assess the quality of antibiotic utilisation after any intervention by administering it regularly. Keywords: Antimicrobial stewardship, Antimicrobial consumption, Hospital, Point prevalence survey, Quality indicators